Application of a modified electrocardiogram‐guided technique for umbilical venous catheterisation in neonates: A retrospective trial. (17th December 2019) - Wu, Liyuan; Peng, Min; Cao, Tian; Yang, Yonghui; Wang, Qin; Luo, Kaiju; Chen, Pingyang
Abstract : Aim: To investigate the effectiveness and safety of modified electrocardiogram (ECG)‐guided technique in umbilical venous catheterisation in neonates. Methods: Sixty‐six critically ill neonates underwent umbilical venous catheterisation with (ECG group) or without (control group) ECG guidance from January 2017 to March 2019. We retrospectively analysed and compared the rate of correct tip placement on first try, unplanned extubation rate and incidence of catheter‐related complications between the two groups. Results: There were 33 patients in each group. The ECG group showed significantly higher rate of correct tip placement on first try ( P < 0.001), lower unplanned extubation rate ( P < 0.001), but identical incidence of catheter‐related complications ( P = 0.492) comparing with the control group. Conclusion: The ECG‐guided technique is an effective and safe method for umbilical venous catheterisation. The connecting method we modified made this technique more practical and can be promoted to areas without access to specific ECG adaptors.